Flexible macrocycles as versatile supports for catalytically active metal clusters. Issue 58 (19th February 2016) - Ryan, Jason D.; Gagnon, Kevin J.; Teat, Simon J.; McIntosh, Ruaraidh D.
Abstract : Here we present three structurally diverse clusters stabilised by the same macrocyclic polyphenol; t -butylcalix[8]arene. Abstract : Here we present three structurally diverse clusters stabilised by the same macrocyclic polyphenol; t -butylcalix[8]arene. This work demonstrates the range of conformations the flexible ligand is capable of adopting, highlighting its versatility in metal coordination. In addition, a Ti complex displays activity for the ring-opening polymerisation of lactide.